Perencanaan Rabat Beton Tahan Retak Untuk Peningkatan Kualitas Jalan Di Desa Laowo Hilimbaruzo - Giawa, Jun Fajar Krisman; Mendrofa, Kevin Berkat; Zebua, Friski Dermawan; Zebua, Dermawan (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The road conditions in Laowo Hilimbaruzo Village, Nias Regency, have significantly deteriorated, disrupting residents' mobility and agricultural product distribution. This community service program aimed to plan and construct a crack-resistant concrete pavement (rabat beton) to improve the quality and durability of rural roads. The implementation method included an initial field survey, the design of a concrete mix incorporating polypropylene fiber additives, technical training for local residents, and a participatory construction approach. The results showed that a 180-meter-long concrete road was successfully built, achieving an average compressive strength of 23.5 MPa and showing no surface cracks during the initial monitoring period. High community involvement and the establishment of a local infrastructure working group demonstrated the effectiveness of the empowerment approach. This program not only resulted in physical infrastructure improvement but also enhanced the technical capacity and institutional strength of the local community. With the right approach, similar initiatives can be replicated in other rural areas as a model for sustainable development based on collaboration and simple technology.